Transaksi Online Terhadap Perubahan Pola Konsumsi Mahasiswa Menurut Perspektif Ekonomi Syariah - Maskur Maskur; Budiman budiman (STAI La Tansa Mashiro, 2023)
With technological advances, it is possible to do activities easily and quickly, including online shopping. In Islam, all life has rules that become guidelines as well as in terms of muamalah, the basis of muamalah law is permissible as long as there is no evidence that forbids it. This research is an empirical research conducted in 2022 which aims to test the hypothesis of online transactions on consumption patterns and how much influence online transactions have on consumption patterns. The method used is quantitative method with technique Based on the results of the research conducted, it is stated that (1) There is no significant influence between Online Shopping on Student Consumption Patterns. This is based on the significance value of the coefficients table with a significance of 0.278> 0.05 and based on the Fcount value of 1.225 < Ftable 4.196 so it can be concluded that the Online Shopping variable (X) has no significant effect on Student Consumption Patterns (Y). (2) The magnitude of the influence of Online Shopping on Student Consumption Patterns is 4%. This can be seen from the correlation value of the relationship (R) which is 0.205 with the output of the coefficient of determination (R square) of 0.042 or 0.042 <1, which implies that the independent variable (Online Shopping) on the dependent variable (Student Consumption Patterns) is 4%.Keywords: Online Transactions, Consumption Patterns, Sharia Economics